A biobased synthesized N-hydroxymethyl starch-amide for enhancing the wet and dry strength of paper products. (1st January 2023) - Marcello, Cornellius; Salam, Abdus
Abstract: The aim of this research was to develop a bio-based paper strength agent for the replacement of petroleum-based paper strength agents. Cationic starch was modified with 2-chloroacetamide in aqueous media. The modification reaction conditions were optimized based on the acetamide functional group incorporated into cationic starch. Further, modified cationic starch was dissolved in water and then reacted with formaldehyde to produce N -hydroxymethyl starch-amide. 1 % N -hydroxymethyl starch-amide was mixed with OCC pulp slurry before preparing the paper sheet for testing the physical properties. The wet tensile index, dry tensile index, and dry burst index of the N -hydroxymethyl starch-amide-treated paper increased 243 %, 36 %, and 38 %, respectively, compared to the control sample. In addition, comparative studies were done between N -hydroxymethyl starch-amide and commercial paper wet strength agent GPAM and PAE. The wet tensile index of 1 % N -hydroxymethyl starch-amide-treated tissue paper was similar to GPAM and PAE, and 2.5 times higher than the control sample. Graphical abstract: Unlabelled Image